Powerful pictures : rock art research histories around the world - Hampson, Jamie, 1973-; Challis, Sam,; Goldhahn, Joakim, (Archaeopress Archaeology, 2022)
Focusing on stunning paintings and engravings from around the world, 16 papers interrogate the driving forces behind global rock art research. Many of the motifs featured were created by Indigenous hunter-gatherer groups; this book sheds new light on non-Western rituals and worldviews, many of which are threatened or on the point of extinction.